2022
DOI: 10.1186/s12931-022-02132-4
|View full text |Cite
|
Sign up to set email alerts
|

The respiratory microbiota alpha-diversity in chronic lung diseases: first systematic review and meta-analysis

Abstract: Background While there seems to be a consensus that a decrease in gut microbiome diversity is related to a decline in health status, the associations between respiratory microbiome diversity and chronic lung disease remain a matter of debate. We provide a systematic review and meta-analysis of studies examining lung microbiota alpha-diversity in patients with asthma, chronic obstructive pulmonary disease (COPD), cystic fibrosis (CF) or bronchiectasis (NCFB), in which a control group based on di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 63 publications
1
17
0
Order By: Relevance
“…Shannon index and Simpson index measure species richness and evenness. Simpson reinforces evenness and Shannon reinforces richness 22 .…”
Section: Resultsmentioning
confidence: 99%
“…Shannon index and Simpson index measure species richness and evenness. Simpson reinforces evenness and Shannon reinforces richness 22 .…”
Section: Resultsmentioning
confidence: 99%
“…First, we showed that SA children tend to have greater bacterial diversity than non-asthmatics. While there appears to be a consensus that a decreased alpha-diversity of the gut microbiome is linked to a declined health status, there is no clear evidence how this generalizes to the microbiomes of the lungs [39].…”
Section: Discussionmentioning
confidence: 99%
“…In human cases, it has been described as an indicator of several disease states 54,55 , and may even be associated with response to therapy in the treatment of certain conditions 56 . Disease has often been associated with a decrease in alpha diversity, but the opposite has also been reported 57 . It is important to note that, in addition to humans, alpha diversity has also been shown to be associated with various diseases in fish as well 58,59 .…”
Section: Discussionmentioning
confidence: 99%